Effects of seasonal variations on sediment-plume streaks from dredging operations. Issue 1 (April 2018) - Kim, Nam-Hoon; Pham, Van Sy; Hwang, Jin Hwan; Won, Nam Il; Ha, Ho Kyung; Im, Jungho; Kim, Youngsung
Abstract: When mixtures of aggregates and water dredged from the seabed are discharged at the surface into the adjacent water from a barge, coarse sediments sink immediately and fine sediments are suspended forming a plume. Recently, elongated plumes of fine sediment were observed by satellites near a dredging location on the continental shelf. Such plume streaks were longer in certain conditions with seasonality than expected or reported previously. Therefore, the present work studied the appearance of sediment plume with field measurements and numerical simulations and explains the seasonally varying restoring force and thicknesses of the surface mixed layer resulting from the vertical density distribution near the surface, along with mixing by hydrodynamic process. The resulting mixtures, after vertical restoring and mixing with the surroundings, determine the horizontal transport of suspended sediments. A numerical model successfully reproduced and explained the results from field measurements and satellite images along with the seasonal variations. Highlights: Image captured by a satellite reported the unexpectedly long streaks of sediment plume from a dredging site. Elongations of plume depend on the seasonal variations of density differences between the mixtures and surface waters. While a long streak is observed, restoring force is too weak to sink the mixtures of sediment and water to the bottom. Seasonal variations of the surface mixed layer thickness significantly affect the development of the elongated plumes.